Association of different oral anticoagulants use with renal function worsening in patients with atrial fibrillation: A multicentre cohort study. Issue 12 (7th June 2020) - Pastori, Daniele; Ettorre, Evaristo; Lip, Gregory Y.H.; Sciacqua, Angela; Perticone, Francesco; Melillo, Francesco; Godino, Cosmo; Marcucci, Rossella; Berteotti, Martina; Violi, Francesco; Pignatelli, Pasquale; Saliola, Mirella; et al.
Abstract : Aims: To investigate the decline of estimated glomerular filtration rate (eGFR) in patients with atrial fibrillation (AF) treated with vitamin K antagonists (VKAs) or non‐VKA oral anticoagulants (NOACs). Methods: Multicentre prospective cohort study including 1667 patients with nonvalvular AF. The eGFR was assessed by the CKD‐EPI formula at baseline and during follow‐up. The primary endpoint of the study was the median annual decline of eGFR according to VKA (n = 743) or NOAC (n = 924) use. As secondary endpoints, we analysed the transition to eGFR <50 mL/min/1.73 m 2 and the eGFR class worsening. Results: Median age was 73.7 ± 9.1 years and 43.3% were women. VKA‐treated patients showed an eGFR decline of −2.11 (interquartile range [IQR] –5.68/−0.62), which was −0.27 (IQR –9.00/4.54, P < 0.001 vs VKAs), −1.21 (IQR –9.98/4.02, P = 0.004 vs VKAs) and −1.32 (IQR –8.70/3.99, P = 0.003 vs VKAs) in patients on dabigatran, rivaroxaban and apixaban, respectively. Transition to eGFR <50 mL/min/1.73 m 2 was lower in dabigatran‐ and apixaban‐treated patients: odds ratio (OR) 0.492, 95% confidence interval (CI) 0.298‐0.813, P = 0.006 and OR 0.449, 95% CI 0.276‐0.728, P = 0.001, respectively. A lower rate of eGFR class worsening was found in all groups of NOACs compared to VKAs. No difference between full and reduced dose of NOAC was found. Subgroup analysis showed that the association between NOAC and eGFR changes was markedly reduced in diabetic patients. Conclusion: Patients prescribed NOACs showed a lower decline of renal function compared to those prescribed VKAs. This effect was partially lost in patients with diabetes.